Trends in the development of education system in Israel - Rina Ben Shabo (PUBLISHINGS of Kostanay State Pedagogical Institute, 2016)
his article deals with the development of the Israeli education system. In order to understand the changes that have occurred in the system we shall note statistical data showing the number of pupils in class, the salaries of teachers, numbers of pupils from the different sectors. In recent years the Israeli education system has undergone important changes. A significant corner was turned in the development of demographic combinations, resources given to the education system have significantly increased and even manpower resources have grown. Each of the teachers in primary schools have been absorbed into a reformed program called «New Horizon», as have a large number of the junior and high school teachers. Also there has been an improvement in the level of education amongst the, so that now most of them have an academic education. The gaps between Jews and Arabs have decreased. However, there is still a long way to go until the level of service in the education system will be fit for the students and their achievements, both in learning and in education, to meet standards that the State of Israel strives to achieve.
Keywords: the development; the education system; аteacher; а student